سيكولوجية الذات المفردة في رواية إرث الرماد لعبدالسلام عمر عصمان (Comprehensive Journal of Science, 2025)
The psychology of the individual self in the novel Inheritance of Ash concerns the study of the human self in terms of its ambiguity and the attempt to comprehend its essence through personality orientations, emotions, and behaviors. The self is viewed as a biological and social entity that influences and is influenced by others. Inheritance of Ash clarifies the abstract image of the self, its behaviors, and its practices. This is reflected in its focus on the individual self at both the personal and collective levels within society, along with the traditions, customs, and conflicts among groups and oppressive forces, and their impact on the outbreak of invasions and wars that negatively contribute to the weakening, collapse, and slow death of the self.From this perspective, it can be said that the individual self combines multiple types—individual, collective, psychological, idealistic, and others—to reach a comprehensive and specific meaning that unites the self with identity to achieve a certain purpose. It further evaluates self-awareness in personality, its capabilities and expectations, and the influence of these on the psyche, through which the individual experiences reassurance, confidence, and self-fulfillment.
Keywords: Psychology, Self, Narrative, Monologue, Dialogue, Inheritance of Ash